Education on the use of herbal medicine against Hypertension with Joyoboyo Health Community, Kediri - Maulida Mazaya; Ratna Surya Alwi; Reza Alrayan; Esti Ambar Widyaningrum; Evi Kurniawati; Maratu Soleha; Mukh Fajar Nasrulloh; Andri Prasetiyo; Inggrid Tania (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Hypertension (high blood pressure) is a major global health concern. According to the National Health Profile (Riskesdas), it was reported that 450.126 cases occurred in Indonesia (2022), with 38.204 confirmed in Kediri Regency (2023), where hypertension has become the most common non-communicable condition in East Java, which was detected in the aged 15 years old. Generally, people still consume conventional medicine to lower their blood pressure. Contrarily, herbal medicine, often regarded as a complementary or alternative option. Thus, educational strategies for integrating herbal medicine into hypertension management are needed. In Kediri, the Joyoboyo health community plays an important role in spreading awareness about hypertension. During the community service activity, 61 Joyoboyo health cadre volunteers participated in these educational sessions to help them share accurate information with the wider community. These sessions covered topics such as correct dosage, possible interactions with prescription drugs, and the importance of evidence-based herbal use for treatment. These points were reinforced through discussion and supported by analyzing the recent clinical research. A statistical evaluation was conducted to assess the program's effectiveness. Overall, the results of this activity underline the need for a multidisciplinary approach combining traditional and scientific knowledge to optimize the management of hypertension.